2023
DOI: 10.1101/2023.01.27.525880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An adult stem-like cell population generates germline and neurons in the sea anemoneNematostella vectensis

Abstract: Most genetic research animals (e.g., vertebrates, insects, nematodes) segregate germline and soma during early embryogenesis. In contrast, some highly regenerative bilaterian (e.g., planarians) and non-bilaterian animals (e.g., hydrozoan cnidarians) retain adult stem cells with both germinal and somatic potentials. As these cells have been studied in only few phyla, their biology and evolution remain mostly enigmatic. Here, we aimed to identify and characterize adult stem cells and their cell lineages in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 99 publications
3
8
0
Order By: Relevance
“…Since we cannot detect primordial germ cells in the nanos2 mutant in Nematostella, we assume that this function is conserved between bilaterians and cnidarians and dates back at least to the common ancestor about 600 million years ago. While this study could not confirm the presence of a pluripotent stem cell population, it has recently been proposed that the piwi1+ and Vasa2+ cell population is the source of gametes as well as SoxB(2)+ neurons based on lineage analyses of transgenic lines, similar to our approach (68). Our data support this claim and confirm through the characterization of nanos2 KO mutants, that the Vasa2+ cell population residing in the septal filament is the source of gametes in Nematostella.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Since we cannot detect primordial germ cells in the nanos2 mutant in Nematostella, we assume that this function is conserved between bilaterians and cnidarians and dates back at least to the common ancestor about 600 million years ago. While this study could not confirm the presence of a pluripotent stem cell population, it has recently been proposed that the piwi1+ and Vasa2+ cell population is the source of gametes as well as SoxB(2)+ neurons based on lineage analyses of transgenic lines, similar to our approach (68). Our data support this claim and confirm through the characterization of nanos2 KO mutants, that the Vasa2+ cell population residing in the septal filament is the source of gametes in Nematostella.…”
Section: Discussionsupporting
confidence: 83%
“…These features are essential criteria for a multipotent stem cell population similar to the interstitial stem cells in Hydra . Interestingly, a transgenic vasa2 line also showed somatic cell type derivatives such as neurons (68). Co-staining of the nanos2 ::mOrange line with Vasa2 antibodies showed partial overlap between Vasa2 positive cells (presumably primordial germ cells) and nanos2 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…She first showed that a population of stem-like cells located adjacent to the gonads gives rise to the germ cells. Intriguingly, however, these cells also produce neural-like cells and therefore represent a putative population of multipotent stem cells in juveniles and adults [ 22 ]. This exciting work lays a foundation for understanding stem cell biology in anthozoans, and for comparisons with stem cells in bilaterians and other cnidarians.…”
Section: Developmental and Stem Cell Biology: New Methods Provide Ins...mentioning
confidence: 99%
“…A A whole Hydra polyp expressing GFP in all neurons imaged by confocal microscopy [ 46 ]. B Close up confocal section of the Nematostella vectensis gastrodermis from a line containing a CRISPR-Cas9 knock-in of GFP into the Piwi1 locus (Green) and the NvSoxB(2)::mOrange2 transgene [ 22 , 47 ]. C A sexual polyp of transgenic Hydractinia symbiolongicarpus bearing the β-tubulin::mScarlet and Piwi1::GFP transgenes [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is plausible that meiosis and female gametogenesis originated in a single eukaryotic ancestor, the degree to which the similarities observed in Drosophila and mammalian oogenesis reflect evolutionarily conserved mechanisms versus convergent evolution, with the rewiring of highly conserved regulatory modules remains uncertain. Ongoing work with various organisms representative of eukaryotic evolution (e.g., [ 10 , 139 , 140 , 141 ]) will undoubtedly contribute to tackling this problem and allow a better understanding of oogenesis evolution.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%